Do We Have A Moral Obligation to Synthesize Organisms to Increase Biodiversity? On Kinship, Awe, and the Value of Life's Diversity - Boldt, Joachim (Bioethics, 2013)
Synthetic biology can be understood as expanding the abilities and aspirations of genetic engineering. Nonetheless, whereas genetic engineering has been subject to criticism due to its endangering biodiversity, synthetic biology may actually appear to prove advantageous for biodiversity. After all, one might claim, synthesizing novel forms of life increases the numbers of species present in nature and thus ought to be ethically recommended. Two perspectives on how to spell out the conception of intrinsic value of biodiversity are examined in order to assess this line of thought. At the cost of introducing two separate capacities of human knowledge acquisition, the ‘admiration stance’ turns out to reject outright the assumption of a synthetic species' intrinsic value and of an imperative to create novel species. The ‘kinship stance’ by contrast does ascribe value to both synthetic and natural species and organisms. Nonetheless, while from this perspective creating novel species may become an ethical demand under certain conditions, it favours changing organisms by getting in contact with them rather than synthesizing them. It is concluded that neither the admiration nor the kinship stance warrants a supposed general moral obligation to create novel species to increase biodiversity.